Students' perception on the selected facets of reputation quotient: a case study of a Malaysian public university - Chan, Tak Jie; Mohd Hasan, Nurul Ain (Africa Development and Resources Research Institute, 2019)
Past empirical studies have shown that specific facets of Reputation Quotient model positively influenced the reputation. However, the relevance of applying the Reputation Quotient model that focuses on the university setting in developing economies is still under researched. Hence, this study aims to examine the perception of current students about the dimensions of Reputation Quotient in one of the Malaysian higher education institutions (HEIs). In particular, the study aims to find out the differences between the subscales of Reputation Quotient pertaining to products and services, social responsibility, vision and leadership, financial performance, and emotional appeal facets. Multistage sampling was employed in this study, whereby simple random sampling and convenience sampling were applied. A quantitative (survey) method was employed in this study, in which questionnaires were distributed to 383 current students (local and international), but with 378 valid responses received. The data were then analyzed using descriptive statistics and one sample T-test. Based on the findings, the current students at the public HEI have a positive view about the reputation of the university. Data revealed that the students perceived positively on the subscale of Reputation Quotient pertaining to the five facets mentioned. The results call upon the management of the public HEI to focus on the dimensions mentioned in order to enhance the good perception and images from various constituents that will increase the survival of the institution in this competitive business market.